A review on mouth dissolving tablets - Manoranjan Sahu; Smitapadma Mohanty; Asish Dev (International Journal of Pharmacy and Analytical Research, 2015)
Now a day’s oral route of drug delivery considered as most convenient and economical method of drug delivery system. But for pediatric, geriatric, and bedridden patients it is difficult to swallow solid dosage form like tablets and capsules and may feel difficulty to take liquid dosage forms because of hand tremor. An active patient who is busy and traveling and may not access to water it’s a problem to administer a drug. By formulating mouth dissolving drug delivery system (MDDDS) all these drawbacks can be overcome. It has the advantage that it can avoid fast pass metabolism too. Mouth dissolving tablets are designed to be dissolved on the tongue rather than swallowed whole. So it will release the drug as soon as it will come in contact with saliva. This review article focused on various techniques involved in manufacturing of mouth dissolving tablets (MDTs) ranged from patented to non patented technologies. Characteristics of MDTs, advantages, disadvantages, factors responsible for sublingual absorption, challenges in formulating mouth dissolving tablets are discussed. This article demonstrate various evaluation tests of mouth dissolving tablets like weight variation, crushing strength, measurement of tablet porosity, friability, wetting time, in-vitro drug release, disintegrating test, modified disintegration test, water absorption ratio and stability studies.